3-D negotiation : powerful tools to change the game in your most important deals - Lax, David A. (Harvard Business School Press, 2006)
"In 3-D Negotiation: Powerful Tools to Change the Game in Your Most Important Deals, David Lax and James Sebinius urge bargainers to look beyond tactics at the table. Indeed, persuasive tactics are only the "first dimension" of the author's 3-D Negotiation (TM) approach, developed from their decades of doing deals and analyzing great dealmakers." "Packed with practical steps and engaging examples, 3-D Negotiation demonstrates how superior setup moves plus insightful deal design can enable you to reach remarkable agreements once you arrive at the table - deals that would be unattainable by standard tactics, no matter how skillful."--Jacket.